AN ANALYSIS OF ERGONOMIC RISK FACTORS ASSOCIATED WITH THE WOOD BLOCK MAKING CRAFT OF PETHAPUR, GUJARAT, INDIA - Bhatt, Vandita; Bhatia, Dr. Reena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The handicrafts sector in India provides employment to a vast number of people contributing to the country's economy; by the vary nature of woodblock making craft, the produce is made with hand- making it labour intensive; spending hours in the same place, health hazards associated occupation. Woodblock makers of Pethapur served as the focal point of the ergonomic study; to render the craft person to be more efficient and productive. The semi structured interview schedule was developed containing a detailed check list for analyzing occupational health hazards using musculoskeletal disorder scale and RULA scale. The results showed that the senior craftsmen experienced pain at various body parts such as joint pain, neck and shoulder pain. It was also discovered that working posture has relation to the body sections that are in pain. It was concluded that there is a need for implementing change in working pattern, workspace arrangement as well as creating awareness amongst the craftsmen about the ergonomic risk factors. The craftsmen need to undergo some physical exercises before performing work which would help in reducing pains.